2017
DOI: 10.1007/s11892-017-0857-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Diabetic Ketoacidosis (DKA)/Hyperglycemic Hyperosmolar State (HHS): Novel Advances in the Management of Hyperglycemic Crises (UK Versus USA)

Abstract: Purpose of ReviewDiabetic ketoacidosis (DKA) and hyperglycemic hyperosmolar state (HHS) are diabetic emergencies that cause high morbidity and mortality. Their treatment differs in the UK and USA. This review delineates the differences in diagnosis and treatment between the two countries.Recent FindingsLarge-scale studies to determine optimal management of DKA and HHS are lacking. The diagnosis of DKA is based on disease severity in the USA, which differs from the UK. The diagnosis of HHS in the USA is based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 44 publications
1
75
0
9
Order By: Relevance
“…Empagliflozin increased levels of serum ketone bodies in Japanese participants with T1DM in this study, as was previously observed in non‐Japanese and Japanese participants with T2DM receiving empagliflozin. Mean serum BHB levels after 4 weeks of empagliflozin treatment were generally <0.5 mmol/L, with the highest individual BHB level at approximately 0.8 mmol/L, below the levels of total ketone bodies seen with physiological ketosis, such as prolonged fasting or exercise (1‐2 mmol/L), and well below levels seen in DKA (>3 mmol/L) . Importantly, special attention was paid to prevention of DKA during the study, including adoption of measures such as avoiding marked reduction in insulin dose.…”
Section: Discussionmentioning
confidence: 99%
“…Empagliflozin increased levels of serum ketone bodies in Japanese participants with T1DM in this study, as was previously observed in non‐Japanese and Japanese participants with T2DM receiving empagliflozin. Mean serum BHB levels after 4 weeks of empagliflozin treatment were generally <0.5 mmol/L, with the highest individual BHB level at approximately 0.8 mmol/L, below the levels of total ketone bodies seen with physiological ketosis, such as prolonged fasting or exercise (1‐2 mmol/L), and well below levels seen in DKA (>3 mmol/L) . Importantly, special attention was paid to prevention of DKA during the study, including adoption of measures such as avoiding marked reduction in insulin dose.…”
Section: Discussionmentioning
confidence: 99%
“…1763 Patients presenting with mild diabetic ketoacidosis who are alert and able to tolerate oral fluids may be able to receive treatment in the emergency department, potentially with oral fluids and subcutaneous insulin, and without need for hospital admission 64. Patients presenting with more severe degrees of metabolic derangement need to be admitted to a hospital unit with trained personnel and resources for intensive monitoring and administration of intravenous fluids, potassium, and insulin.…”
Section: Acute Managementmentioning
confidence: 99%
“…The ADA and the Joint British Diabetes Societies for Inpatient Care have both published guidelines for management of diabetic ketoacidosis, but these guidelines have several differences. These differences are primarily due to lack of published evidence to guide treatment in many areas 63. Despite this, the ADA guideline has been widely distributed, is used internationally, and has been cited more than 600 times 63.…”
Section: Acute Managementmentioning
confidence: 99%
See 2 more Smart Citations